Pengaruh Promosi Penjualan, Daya Tarik Iklan Internet, dan Kualitas Website Terhadap Pembelian Impulsif - Maria Fernanda (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
This goal of this study is to find out whether sales promotion, internet advertising, and website quality influence impulsive buying. This study was conducted using descriptive study approach. Subject of this study were consumers in Jakarta who have made purchase during last 6 months. Data in this study was obtained from questionnaire which distributed to 150 respondents. Method used in sampling was non probability sampling with convenience sampling. The collected data was tested using multiple regression analysis method in SPSS. The result of this study showed, each variables : sales promotion, internet advertising, and website quality have significant and positive effect on impulse buying.